Navigating the storm: Ethical consideration to climate justice and sustainable health equity in Africa - Adetayo Emmanuel Obasa (The Journal of Climate Change and Health)
Africa bears a disproportionate burden of climate change, despite contributing minimally to global greenhouse gas emissions. This article explores the ethical imperatives of addressing climate-induced health disparities in Africa, particularly through the lens of climate justice and the African philosophy of ubuntu. In Sub-Saharan Africa, approximately 700 million people live on less than $2.15 per day, falling below the extreme poverty line. Low-income communities disproportionately suffer from the negative impacts of climate change. These populations face a multifaceted crisis that requires clear, ethical, and specific solutions tailored to their unique needs. Drawing on theories of distributive, corrective, and participatory justice—as well as Rawlsian and utilitarian ethics—the paper critiques current global mitigation and adaptation strategies for their failure to adequately support African priorities. It further advances the case for integrating grassroots participation, community-based solutions, and inclusive governance. By prioritizing health equity, environmental justice, and ethical policymaking, the article proposes practical recommendations that align short-term needs with long-term sustainability. This article charts a pathway toward just and inclusive climate policies by arguing for a transformative response rooted in justice, solidarity, and African agency—prioritizing the needs of the most affected while fostering resilience and sustainability for future generations.